Nalar Integrasi Fikih dan Psikologi Keluarga dalam Pandangan Hakim Agama Jawa Timur Tentang Hak Asuh Anak Pasangan Murtad - M. Ghufron; Moh. Ali (State Islamic University (UIN) of Sunan Ampel, 2020)
One of the causes of divorce which was decided by a Religious Court judge was because of the apostasy of one of the spouses. Divorce due to apostasy leaves problems in parenting. To whom the child custody will be given must be considered by the judge. This research is empirical research (field study) with fiqh and family psychology approach to get an understanding of the basic considerations of judges in establishing child custody in the case of an apostate partner. Through interviews and documentation, the study found, that the consideration of judges based on three things: first, normative basis, which is based on the consideration of Constitution No. 1 of 1974, Compilation of Islamic Law, Constitution No. 7 of 1989 Jo. Constitution Number 30 of 2006 concerning Childcare, and Number 23 of 2002, Supreme Court jurisprudence Number 210 / K / AG / 1990. Second, fiqh basis, which refers to the requirements of the Hadhanah which are in line with fiqh and the provisions of the Hadhanah based on Syafii's Madzab. Third, the psychological basis, which considers all psychological problems related to children. By using this integrative analysis the judge considers that the requirements for Muslims to care for children are in line with psychological values, that the family must provide Islamic education to shape the child's mental spirit.